Food packaging and preservation - Grumezescu, Alexandru Mihai; Holban, Alina Maria (Academic Press, 2018)
This book explores recent approaches to preserving and prolonging safe use of food products, including packaging techniques and materials. -- Resumé vydavatele
Keywords: potraviny; konzervování potravin; balení potravin; hygiena potravin; foodstuffs; food preservation; food packaging; food hygiene; příručky; elektronické knihy; handbooks and manuals; electronic books